The Effect of High-Intensity Interval Training and Continuous Training on the Desnutrin Gene Expression in the Subcutaneous Adipose Tissue and the Quadriceps Femoris Muscle Tissue of Obese Male Rats - Saeed Rahmaty; Abas Ali Gaeini; Mojtaba Dolatshahi; Siross Choobineh (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Desnutrin is an enzyme that catalyzes the first step of cytoplasmic triacylglycerol lipolysis from white adipose tissue and several other tissues, which are disrupted by the obesity and metabolic syndrome. Objectives. The aim of this study was to compare the effect of high-intensity interval training and continuous training on the desnutrin gene expression in the subcutaneous adipose tissue and the quadriceps muscle tissue of obese male rats. Methods. For this purpose, after 12 weeks on a high-fat diet, 30 Wistar rats were divided into two groups: continuous training (n =10) and high-intensity interval training (n=10). Continuous (80%VO2max) and high-intensity interval exercise training (100%VO2max) sessions were conducted according to the principle of overload for six weeks and six sessions per week. Forty-eight hours after the last training session, the abdominal subcutaneous adipose tissue and quadriceps muscle tissue were extracted, and the expression level was assessed using the RT-PCR method. Results. The study showed that the difference between high-intensity interval and continuous training on the desnutrin gene expression subcutaneous adipose tissue was significant (p=0.004), but there were no significant differences (p=0.415) between them in the quadriceps femoris muscle tissue. Conclusion. According to the findings of the present study, in the adipose tissue, continuous training has a greater effect on the desnutrin gene expression than high-intensity interval training. In the muscle tissue, however, there is no difference between these two training exercises.